Partisipasi Masyarakat Dalam Pengelolaan Desa Wisata Bongkasa Pertiwi Di Kabupaten Badung - Karnayanti, Ni Made Devi; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2019)
The purpose of this research is to know community participation in managing Bongkasa Pertiwi Village in Badung Regency. In this study using primary data sources and secondary data sources, while the type of data used is qualitative data. Methods of data collection through observation, interview and documentation study. Determination of informants in this study using purposive sampling technique. Data analysis used is qualitative data analysis technique and constrained by 4A concept, rural tourism concept, management concept and society participation concept. The research results obtained is Public participation is not optimal in managing tourist village, lack of public participation in planning, organizing, implementation and supervision because of the weakness of role of tourism village manager, low quality of human resources, socio-economic life of the community and lack of cooperation. Keywords: Rural Tourism, Management, Community Participation